MANAJEMEN KURIKULUM MADRASAH BERBASIS PESANTREN DI MADRASAH ALIYAH AL MUSYAFFA’ SEMARANG - Mufarriha, Ainis Shofwah; Amir Mahmud; Tri Suminar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
School-aged juvenile deliquency is a social phenomenon that continues to increase and become a serious challenge to the world of education, especially in the Semarang City area. Various forms of deviant behavior such as violence, illegal racing, and low self-control in adolescents indicate that formal education has not been fully able to shape the character and morals of students comprehensively. This study aims to analyze the role of Islamic boarding school-based madrasa curriculum management as a preventive solution in overcoming delinquency in school-aged juveniles, by emphasizing the integration of academic education and religious character development. This study uses a qualitative approach with literature study methods and conceptual analysis of curriculum management practices in Islamic boarding school-based madrasas at MA Al Musyaffa' Semarang. The results of this study indicate that planned, integrated curriculum management, and orientation towards Islamic boarding school values ​​such as discipline, exemplary behavior, habituation of worship, and strengthening of morals play a significant role in shaping adolescent self-control and social behavior. The implication is that lessons are more easily absorbed by students, learning outcomes can be completed well, and the resulting output is of high quality. Mastery of the yellow books (kitab kuning), Arabic and English language, and memorization of 30 chapters (juz) Holy Quran within six months, which are prioritized, have achieved a 95% success rate. Thus, the Islamic boarding school-based madrasa curriculum management at MA Al Musyaffa' Semarang has strategic potential as a preventative measure against juvenile delinquency through a holistic, sustainable educational approach based on moral and spiritual values. Keywords: Juvenile deliquency, madrasa curriculum, Islamic boarding school.